2002
DOI: 10.1002/jsfa.1122
|View full text |Cite
|
Sign up to set email alerts
|

L‐Phenylalanine ammonia‐lyase activity and concentration of phenolics in developing olive (Olea europaea L cv Arbequina) fruit grown under different irrigation regimes

Abstract: Changes in L-phenylalanine ammonia-lyase (PAL, EC 4.3.1.5) activity and total phenolic, ortho-diphenolic and fat contents of olive¯esh in response to different irrigation treatments applied to olive tree cv Arbequina were studied during fruit ripening. Results indicate that the fat content of olivē esh at harvest was not affected by irrigation, although olives from the most heavily irrigated treatment reached their ®nal fat content (dry weight) earlier than those from other irrigation treatments. PAL activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
123
4
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 22 publications
17
123
4
4
Order By: Relevance
“…For other plants (Mangifera indica), the phenolic compound content is influenced by their response to light (Tovar et al, 2002). However, no significant difference in content of total phenolic compounds, PAs, 3-DA, or flavan-4-ols was found between the grain of sorghum varieties resistant or susceptible to photoperiod.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…For other plants (Mangifera indica), the phenolic compound content is influenced by their response to light (Tovar et al, 2002). However, no significant difference in content of total phenolic compounds, PAs, 3-DA, or flavan-4-ols was found between the grain of sorghum varieties resistant or susceptible to photoperiod.…”
Section: Resultsmentioning
confidence: 93%
“…) and abiotic (drought, temperature, photoperiod, nutrient deficiencies, etc.) stresses induce phenylalanine ammonia lyase (PAL; EC 4.3.1.5) synthesis (Chalker-Scott and Fuchigami, 1989;Tovar et al, 2002). PAL activity has been detected in the green shoots and leaves (Stafford, 1969;Mohan et al, 1988) of sorghum, and in sorghum, the infection of the plant with pathogens involves a rapid accumulation of PAL mRNA (Cui et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those authors registered a significant increase of weight, volume, and flesh:pit ratio. Recently, other authors (Patumi et al 2002;Tovar et al 2002;Marsilio et al 2006;García et al 2014) reported that drupes from irrigated olive trees are characterized by lower contents in phenolic compounds than those from not irrigated trees, evidencing an effect of the irrigation on the chemical composition of the drupes. However, the effects of different regulated deficit irrigation (RDI) strategies applied to olive orchards have been evaluated, so far, on the drupes for oil extraction rather than table olive production (Goldhamer 1999;Iniesta et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to Romero et al (2002), this fact can be due to the activation of the phenolic biosynthesis pathway. As observed in Tovar et al (2002), this could have been provoked by the stress suffered under RDI, which leads to an increase in l-phenylalanine ammonia lyase activity, which is the main enzyme in this metabolic pathway.…”
Section: Analysis Of Bioactive Compoundsmentioning
confidence: 92%